174 Addressing elder abuse in the united states: federal guidelines for adult protective services. (1st September 2016) - Greenlee, Kathy; Walker, Edwin; Whittier-Eliason, Stephanie
Abstract : Background: Elder abuse—any knowing, intentional, or negligent act by a caregiver or any other person that causes harm or a serious risk of harm to people over the age of 60—impacts at least 6% of older adults across the globe, but only 17% of countries have collected national data to measure the scope of the problem. 1 In the U.S., Adult Protective Services (APS) systems play a critical role in identifying and responding to abuse, neglect, self-neglect, and financial exploitation faced by older adults and persons with disabilities; however, APS varies across and within states, lacking uniform guidance that hinders cross-jurisdictional cooperation, information sharing, and investigation. Further, lack of standardised service provision contributes to the absence of critical supports for victims. To address this gap, in 2014, the Administration for Community Living (ACL) established the Elder Justice and Adult Protective Services Program to support state APS systems to provide consistent, evidence-based services, so victims receive quality support regardless of their state or jurisdiction. Methods: The program seeks to improve APS systems nationwide by: developing federal guidelines to provide a standard for APS services through the input of expert stakeholders; implementing a National Adult Protective Services Data Collection System; and, funding demonstration grants to 11 states to enhance their APS systems through innovative practices. Results: Preliminary results demonstrate program success, with participation from more than 75% of state and territory jurisdictions in the data collection effort, and 600+ pages of public comments in support of the national guidelines. Phase 1 results (2 years of these collective efforts) are anticipated in June 2017. Conclusions: ACL's efforts to facilitate the development of a coordinated, national approach to APS systems shows promise for enhancing state and local responses to investigating and responding to abuse, neglect, and exploitation of older adults, incorporating data collection to guide current practice and future research, evidence-based practices, and uniform response standards. Note: Global Status Report on Violence Prevention 2014. World Health Organisation, 2014.